2018
DOI: 10.1007/s42000-018-0041-5
|View full text |Cite
|
Sign up to set email alerts
|

The low levels of bone morphogenic protein-4 and its antagonist noggin in type 2 diabetes

Abstract: BMP-4 and noggin levels were lower in the diabetic group. High BMP-4 levels were significantly associated with albuminuria. Further studies are warranted to determine the role of BMP-4 in the pathogenic processes underlying albuminuria and hyperglycemia in patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Although BMP2 and BMP4 have important roles in the development of osseous tissues, their uncontrolled levels were associated with the progression of many diseases. For example, they have been identified as risk factors for type-2 diabetes, coronary artery diseases, diabetic retinopathy and endothelial cell dysfunction [43,[45][46][47]. Nevertheless, few studies have investigated the role of BMP2 and BMP4 in tissues affected by AMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although BMP2 and BMP4 have important roles in the development of osseous tissues, their uncontrolled levels were associated with the progression of many diseases. For example, they have been identified as risk factors for type-2 diabetes, coronary artery diseases, diabetic retinopathy and endothelial cell dysfunction [43,[45][46][47]. Nevertheless, few studies have investigated the role of BMP2 and BMP4 in tissues affected by AMD.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the BMP4 was below the detection limit of 3.68 pg/mL in the sera of the control group which might seem contrary to other reports that showed variable levels of BMP4 in the serum of normal human subjects and these levels are over a wide range between 0.6 pg/mL to 127 ng/mL Such differences can be explained by the usage of different ELISA kits with different cut off values. For example, Yurekli et al [46] reported a very high level of BMP4 (127 ng/mL) in the sera of normal human subjects by using the local commercial ELISA assays (Shanghai, China). On the other hand, Son et al [52] used an ELISA-based system similar to what we have used in this study and reported a very low level of BMP4 in the serum of normal subjects (0.63 ± 0.41 pg/mL).…”
Section: Discussionmentioning
confidence: 99%
“…BMP-4, which belongs to the TGF-β superfamily, can directly induce osteogenic differentiation of BMSCs and osteoblasts through the Smad signaling pathway [ 38 ]. Recently, many studies have reported that the expression of BMP-4 is decreased in the serum of patients with DM and the calvarial defects of a DM rat model [ 39 , 40 ]. In addition, Martínez et al and Valencia et al reported that BMP-4 could induce macrophages to the M2 type by enhancing the secretion of IL-10 [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…BMP‐4 levels were inversely related to carotid atherosclerosis, and individuals with diabetes mellitus had lower serum concentrations of both BMP‐4 and the antagonist noggin 16 . It was postulated that once the levels of BMP‐4 begin to increase, the concentrations of its antagonists may also start to rise to counterbalance the action of BMP‐4 31 . Individuals who suffered from chronic kidney disease (CKD) and coronary artery disease had increased serum levels of BMP‐4, whereas patients without CKD did not vary from one another in this regard 32 .…”
Section: Discussionmentioning
confidence: 99%